FY2015 Administrative and Capital Expenses and Output Cost Estimates. (Policy Papers; Policy Paper, 2015)
The administrative expenditure outturn for FY2015 reflects continued budget discipline, as new demands and initiatives were accommodated through reprioritization and better use of existing resources within an unchanged envelope. The overall budget utilization rate of 98 percent was achieved through more efficient personnel management practices and effective reallocation of resources from underutilized areas to areas of emerging pressure. In terms of outputs, the Fund continued its focus on addressing global policy challenges and reducing vulnerabilities. Resources allocated to multilateral surveillance, oversight of the global systems and capacity development increased while bilateral surveillance and lending declined moderately, in line with easing of crisis-related work. Spending by country reflects a continued shift towards a more risk-based approach, consistent with the established priorities. Capital expenditures mainly reflected the major renovation of the HQ1 building and improvements in information technology infrastructure and security to better support the staff's work and protect information assets.